Penggunaan Media Kartu Tebak Kata untuk Meningkatkan Keterampilan Berfikir Kritis Siswa pada Mata Pelajaran Bahasa Indonesia Kelas III Sekolah Dasar - Nunuy Nurlina; Rosi Iskandar (MJI Publisher by PT Mitra Jurnal Indonesia, 2023)
Abstract This study aims to explore the use of word guessing game learning method in enhancing students' critical thinking skills. This method was implemented with third-grade students at SDN 1 Sajira Mekar through two cycles of learning. Data on students' learning outcomes were collected through pretests and posttests, as well as observations of learning activities. The results showed a significant improvement in students' learning outcomes from cycle I to cycle II, with the percentage of students who passed learning increasing from 42.83% to 89.28%. Furthermore, there was also a significant improvement in students' critical thinking abilities, as reflected in their enhanced abilities to analyze, evaluate, and make decisions. The word guessing game learning method proved to be effective in creating an interactive, enjoyable learning environment that motivates students to engage earnestly in learning. Thus, this method can be a beneficial alternative for educators to improve students' learning outcomes and critical thinking skills. Abstrak Penelitian ini bertujuan untuk mengeksplorasi penggunaan metode pembelajaran permainan tebak kata dalam meningkatkan keterampilan berfikir kritis siswa. Metode ini diimplementasikan pada siswa kelas III di SDN 1 Sajira Mekar melalui dua siklus pembelajaran. Data hasil belajar siswa dikumpulkan melalui pretest dan posttest, serta observasi kegiatan pembelajaran. Hasil penelitian menunjukkan peningkatan yang signifikan dalam hasil belajar siswa dari siklus I ke siklus II, dengan persentase siswa yang tuntas belajar meningkat dari 42,83% menjadi 89,28%. Selain itu, terjadi juga peningkatan yang signifikan dalam kemampuan berfikir kritis siswa, yang tercermin dalam peningkatan kemampuan siswa dalam menganalisis, mengevaluasi, dan mengambil keputusan. Metode pembelajaran permainan tebak kata terbukti efektif dalam menciptakan lingkungan pembelajaran yang interaktif, menyenangkan, dan memotivasi siswa untuk belajar dengan sungguh-sungguh. Dengan demikian, metode ini dapat menjadi alternatif yang bermanfaat bagi pendidik dalam meningkatkan hasil belajar dan keterampilan berfikir kritis siswa.